EVALUATION OF FINANCIAL MANAGEMENT AND ITS IMPACT ON THE PERFORMANCE-BASED BUDGET OF THE BANDUNG CITY HEALTH OFFICE - Fila Azizah Ismail (UPT Publikasi Ilmiah UNISBA, 2025)
This study aims to analyze the effect of regional financial management on the effectiveness of performance-based budgeting at the Bandung City Health Office. Effective regional financial management is expected to increase the allocation and efficient use of the budget, which in turn will contribute to improving organizational performance. This study uses a quantitative approach with a sample of 60 respondents consisting of employees who are directly involved in the budget management process at the Bandung City Health Office. The data collected were analyzed using the Structural Equation Modeling (SEM) method with the help of SmartPLS 3.0 software. The results showed that local financial management has a positive and significant influence on the effectiveness of performance-based budgeting. The influential factors include budget planning, supervision, and transparent and accountable financial reporting. These findings provide important implications for local governments, especially the Bandung City Health Office, to strengthen the local financial management system to support the achievement of more optimal performance targets.